2020
DOI: 10.1200/jop.19.00152
|View full text |Cite
|
Sign up to set email alerts
|

Lay Health Worker-Led Cancer Symptom Screening Intervention and the Effect on Patient-Reported Satisfaction, Health Status, Health Care Use, and Total Costs: Results From a Tri-Part Collaboration

Abstract: PURPOSE: Poor patient experiences and increasing costs from undertreated symptoms require approaches that improve patient-reported outcomes and lower expenditures. We developed and evaluated the effect of a lay health worker (LHW)-led symptom screening intervention on satisfaction, self-reported overall and mental health, health care use, total costs, and survival. METHODS: From November 1, 2015, to September 30, 2016, we enrolled in this study all newly diagnosed Medicare Advantage enrollees with stage 3 or 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…We excluded 1 clinic because it was involved in the previously reported intervention. 17 We enrolled all CareMore Medicare Advantage beneficiaries with newly diagnosed solid tumors or hematologic malignant neoplasms in these 9 clinics and excluded patients who did not receive medical oncology care. Patients were screened by a new patient coordinator, enrolled from November 1, 2016, to October 31, 2017, and followed up for 12 months after enrollment or until death, whichever was first.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 1 clinic because it was involved in the previously reported intervention. 17 We enrolled all CareMore Medicare Advantage beneficiaries with newly diagnosed solid tumors or hematologic malignant neoplasms in these 9 clinics and excluded patients who did not receive medical oncology care. Patients were screened by a new patient coordinator, enrolled from November 1, 2016, to October 31, 2017, and followed up for 12 months after enrollment or until death, whichever was first.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…15,16 A lay health worker (LHW)-led (ie, personnel who are not clinically trained) symptom screening intervention for adults with advanced cancer was previously developed. 17 The goal was to proactively identify symptoms to prevent psychological and physical distress and decrease acute care use. The LHW was trained to assess symptoms and relay them to a supervising physician assistant (PA), who conducted any necessary interventions.…”
Section: Introductionmentioning
confidence: 99%
“…7 In 3 pilot projects across the United States, we demonstrated effectiveness of this approach on improved patient experiences with care, reduced cancer symptom severity, and reduced acute care use and total costs of care. [14][15][16] Between 2013 and 2016, 2 hospital-based and 3 outpatient community-based clinics implemented this program in their cancer clinics.…”
Section: Introductionmentioning
confidence: 99%
“…All the studies were implemented in Europe and North America (ten of them in the United States and Canada). Of the 16 studies identified, eight had a randomized clinical trial design [ 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 ], six were observational studies [ 28 , 29 , 30 , 31 , 32 , 33 ] and two were economic evaluations [ 22 , 34 ]. Of the clinical trials, five reports [ 20 , 24 , 25 , 26 , 27 ] were randomized controlled trials with a high-quality design, whereas two [ 19 , 23 ] were research letters that communicated brief reports of data.…”
Section: Resultsmentioning
confidence: 99%
“…Among the observational studies, one had a retrospective matched cohort design [ 28 ], whereas four used a prospective-cohort design to examine the consequences of implementing a patient-reported symptom strategy in clinical practice [ 30 , 31 , 32 , 33 ]. The remaining study compared a patient-reported symptom strategy prospectively with a historical cohort [ 29 ].…”
Section: Resultsmentioning
confidence: 99%